Modeliranje višinske in debelinske rasti dominantnih dreves ter ocenjevanje indeksov produkcijske sposobnosti gozdnih rastišč - Andrej Bončina (Slovenian Forestry Institute, 2021)
Modeling the height and diameter growth of trees is an important part of forest management. Growth models provide the basis for determining the thinning regime, target tree dimensions and optimal proportions of developmental phases of forest stands. We developed individual height growth models for dominant Norway spruce (Picea abies (L.) Karst) and European beech (Fagus sylvatica L.) in two forest types (sessile oak-European beech forests and pre-Alpine silver fir-European beech forests). Based on the models, the site productivity index (SPI), defined as the dominant tree height at a diameter of 45 cm, was determined for spruce and beech in both forest types. Based on the diameter increment of the dominant trees, the age of trees in regard to their diameter was calculated, which was the basis for Height-Age modeling. The site productivity index (SPI) of spruce in sessile oak-beech forests and pre-Alpine silver fir-European beech forests is higher than that of beech: 31.3 and 29.7 vs 28.7 and 27.9, respectively. Estimated site indices (SI; dominant tree height at the age of 100 years) in sessile oak- European beech forests and pre-Alpine silver fir-European beech forests were 33.4 and 32.0 for spruce, and 29.0 and 27.0 for beech, respectively. Using the described procedure, it is possible to determine indices of site productivity of spruce and beech (SI and SPI) in the selected forest habitat types. Testing the procedure in other forest types and for other tree species is suggested.